Determinant of Efficiency in the Indonesian Islamic Banks - Aliyah, Hikmatul; Hamid, Abdul; Al Arif, Mohammad Nur Rianto (Faculty of Economic and Business, Universitas Islam Negeri Syarif Hidayatullah, 2023)
This study aims to analyze the factors that influence the level of efficiency of Islamic commercial banks in Indonesia. The research employs a panel data analysis and a non-parametric Data Envelopment Analysis (DEA) to measure the level of efficiency. The panel data analysis showed that company size, profitability, liquidity, and management significantly affect the level of efficiency of Islamic banks in Indonesia, while capital and financing risk have no significant impact. The efficiency of Islamic banks in Indonesia should be maintained by balancing the distribution of assets, ensuring portfolio diversification, maintaining sufficient liquidity, and paying attention to management quality. The originality of this study, to the best of the author's knowledge, is that it is the first study to examine the determinants of efficiency in Indonesian Islamic commercial banks using quarterly data from the period of 2015-2020. As a result, the data analyzed has a sufficient amount.JEL Classification: C02, C14, C23, G01How to Cite:Aliyah, H., Hamid, A., & Al Arif, M. N. R. (2023). Determinants of Efficiency in the Indonesian Islamic Banks. Signifikan: Jurnal Ilmu Ekonomi, 12(1), 161-174. https://doi.org/10.15408/sjie.v12i1.30376.